Keterbukaan Informasi Publik melalui SID dari Perspektif Masyarakat Desa Senaung, Kecamatan Jambi Luar Kota, Kabupaten Muaro Jambi - Septiyandri Sya’bani Zidane; Adrian Dwiki Prasetyo; Grace Nastasya Br Sembiring; Deticia Naca (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Public information disclosure is a government duty to fulfill the public's right to information. One of the village government's efforts to support public information disclosure is realized through the Village Information System (SID). The purpose of this study was to analyze public information disclosure through the SID from the perspective of the Senaung Village community. The method used was descriptive qualitative, with data collection techniques through interviews and observations of the village website. The Kristianten information transparency theory was used, focusing on indicators of document availability and accessibility, as well as the clarity and completeness of information. The results of this study indicate that public information disclosure through the SID in Senaung Village is still suboptimal. The village website is still difficult to access, information is incomplete and rarely updated, and not all residents are aware of the village website's existence. The information provided is also still limited to administrative services and does not include information such as the Village Budget (APBDes) and village funds.